2016
DOI: 10.1177/0954410016654180
|View full text |Cite
|
Sign up to set email alerts
|

Side force over slender body with rings at different location at subsonic speed

Abstract: Investigations have been made adopting experiments and computations on an ogive-nosed slender body at different angles of attack and Reynolds number of 29,000 based on the model base diameter diameter. The results indicated an increase in the side force at large angles of attack, which is mainly due to the presence of asymmetric vortices in the leeward of the body. The inclusion of a rectangular cross-sectioned ring in the initial portion of the body reduced the side force at higher angles of attack. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Since the flow appears to be in a quasi-steady state at high angles of attack 6 , hence the measurement was made for a time of 5 s with a sampling frequency of 500 samples/ second. To reduce the side force, a rectangular cross-sectioned circumferential ring having a width of 2 mm and variable height was used [5][6][7][8] . An effort was made to obtain the effect of rings on the rolling moment of the slender body.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the flow appears to be in a quasi-steady state at high angles of attack 6 , hence the measurement was made for a time of 5 s with a sampling frequency of 500 samples/ second. To reduce the side force, a rectangular cross-sectioned circumferential ring having a width of 2 mm and variable height was used [5][6][7][8] . An effort was made to obtain the effect of rings on the rolling moment of the slender body.…”
Section: Methodsmentioning
confidence: 99%
“…The study of the side force over a slender body at high angles of attack has been under consideration since the 1950s [1][2][3][4][5][6][7][8][9][10][11] . Slender bodies with a pointed nose subjected to fly at high incidence experience a large side force and yawing moment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations on similar Reynolds number are reported in the literature and have been previously discussed. Based on the results reported by Kumar and Prasad (2016b;2017) and Lua et al (2000) for ogive-nosed slenderbodies, a rectangular cross-sectioned ring reduced the side force at different α for the case of a cone-cylinder body, type of body expected to have lesser axial force at lower angles of attack, which, in turn, can reduce the drag. However, the flow can be extremely complicated over a cone-cylinder body during maneuvers when it experiences high angles of attack and low Reynolds number.…”
Section: Introductionmentioning
confidence: 94%
“…Leu et al (2005) showed the decrease in the side force using microballoon actuators over a cone-cylinder body. In recent times, experiments and computations carried out by Kumar and Prasad (2017) showed that the use of rings reduces the side force over an ogive-cylinder body. Based on the literature, it is evident that slender-body with conical nose has the advantage of lower axial force and drag in comparison to the other nose shapes.…”
Section: Introductionmentioning
confidence: 99%